2020
DOI: 10.1002/solr.201900510
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Laser‐Scribed Mo Groove Shape on Highly Efficient Zn(O,S)‐Based Cu(In,Ga)Se2 Solar Modules

Abstract: In this work, the effects of the Mo groove (P1 line) shape on the quality and performance of final modules are investigated. A gradual sloped Mo edge is successfully realized by controlling the laser beam parameters and incidence directions. As a comparison, a sharp vertical Mo edge is also investigated. With the traditional sharp vertical groove shape, voids, cracks, and peel‐offs near the abrupt step edge of P1 lines are often found to grow within the Cu(In,Ga)Se2 (CIGS) layer and induce unwanted growth beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Having employed only scalable deposition techniques (blade coating and vacuum deposition) for all 12 layers of the fabricated 2TPT-SMs, the feasibility of upscaling this technology is proven. The demonstrated GFF of our tandem module is comparable to other thin-film PV technologies, such as tandem thin-film silicon photovoltaics (~98% GFF) 29 and CIGS photovoltaics (~93% GFF) 55 . It is noteworthy that the laser set-up applied in this work uses a rather conventional and inexpensive nanosecond laser that is less complex than the widely used picosecond or femtosecond lasers for thin-film solar module patterning in laboratory-scale modules.…”
Section: Non-destructive Scalable Processing Of Tandem Architecturementioning
confidence: 58%
“…Having employed only scalable deposition techniques (blade coating and vacuum deposition) for all 12 layers of the fabricated 2TPT-SMs, the feasibility of upscaling this technology is proven. The demonstrated GFF of our tandem module is comparable to other thin-film PV technologies, such as tandem thin-film silicon photovoltaics (~98% GFF) 29 and CIGS photovoltaics (~93% GFF) 55 . It is noteworthy that the laser set-up applied in this work uses a rather conventional and inexpensive nanosecond laser that is less complex than the widely used picosecond or femtosecond lasers for thin-film solar module patterning in laboratory-scale modules.…”
Section: Non-destructive Scalable Processing Of Tandem Architecturementioning
confidence: 58%
“…First, a 30 nm Zn­(O,S) layer was deposited on the CIGS surface based on the CBD method. For details, please refer to our previous works. ,,, After that, 50 nm Zn 0.74 Mg 0.26 O and 300 nm Al/ZnO layers were deposited by using RF sputtering as the window layer of the device. Finally, an electron beam-vaporized Al grid was used as the electrode to form the complete device.…”
Section: Methodsmentioning
confidence: 99%
“…Using glass-side laser ablation produced more delamination and microcracks due to the pressure created by the plasma expansion, which caused shockwave formation, film deformation, and brittle material cracking. New findings show that crack formation can also depend on the obtained groove profile; groove shapes with sharp vertical edges are more prone to void formation, cracking, and peeling-off in the deposited material than gradually sloped edge scribes [54]. It has been shown that even employing ultrashort pulse lasers could n eliminate these defects for a-Si P2 scribing [98,99].…”
Section: Microstructure and Surface Morphologymentioning
confidence: 99%
“…Scribe depth selectivity and cross-sectional profile Selective laser scribing is an essential feature of assessing the scribe quality, which is strongly impacted by laser parameters [54]. It has been referred to as a scribing process in which a desired depth or layer is ablated entirely without removing or damaging the underlying material [29].…”
mentioning
confidence: 99%